2010
DOI: 10.1073/pnas.0912629107
|View full text |Cite
|
Sign up to set email alerts
|

Rate, molecular spectrum, and consequences of human mutation

Abstract: Although mutation provides the fuel for phenotypic evolution, it also imposes a substantial burden on fitness through the production of predominantly deleterious alleles, a matter of concern from a human-health perspective. Here, recently established databases on de novo mutations for monogenic disorders are used to estimate the rate and molecular spectrum of spontaneously arising mutations and to derive a number of inferences with respect to eukaryotic genome evolution. Although the human per-generation mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

47
621
5
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 719 publications
(684 citation statements)
references
References 55 publications
47
621
5
11
Order By: Relevance
“…First, there are likely to be additional layers of repair mechanisms in germ cells, which would buffer replication timingdependent accumulation of mutations. Supporting this, germ-line mutation rates are known to be lower than somatic mutation rates 16 . The exact mechanism would become clear with advances in our understanding of the DNA repair in germ and somatic cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…First, there are likely to be additional layers of repair mechanisms in germ cells, which would buffer replication timingdependent accumulation of mutations. Supporting this, germ-line mutation rates are known to be lower than somatic mutation rates 16 . The exact mechanism would become clear with advances in our understanding of the DNA repair in germ and somatic cells.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, somatic mutations would be restricted to the progeny of the mutated cells, but germ-line mutations would be propagated to all cells in an organism, increasing the chance of exerting deleterious effects in some cell types. The observation that the somatic mutation rate per generation is higher than the germ-line mutation rate 16 raises an interesting notion that multicellular organisms have evolved to optimize somatic and germ-line mutation rates, so that an organism can keep individual cells viable during its lifetime while passing sufficiently intact genetic information to its offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data confirm and extend these results to the entire genome. Mutational data from a variety of sources have confirmed that in almost all organisms spontaneous mutations are dominated by G:C > A:T transitions, a bias that tends to drive genomes toward greater A:T content (28). However, the G:C content of genomes varies widely, so some selective pressure or nonadaptive mechanism must drive genomes back toward G:C-richness.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure allows very precise estimates, but introduces systematic bias toward higher substitution rates and longer branch lengths because a new lineage can leave a fossil record only after its origin, never beforehand (1). Now, widespread resequencing, initially of de novo Mendelian genetic disorders (2,3) and later of whole genomes in parent-offspring trios (4), has allowed direct comparisons of parent and offspring genomes. The most commonly used, but now outdated, estimate of the mutation rate was 2.4 × 10 −8 changes per nucleotide per generation (5).…”
mentioning
confidence: 99%